Performance Analysis of a 90mm Multi Launcher Missile System Integrated with Radar for Vital Object Air Defense Against High Speed and Stealth Aerial Threats - Nur Rachman Supadmana Muda (ITEGAM-JETIA)
Modern air threats, such as drones and missiles in salvo, pose significant challenges to the defense of vital objects. Traditional air defense systems are limited to small, agile and low-cost targets, and are constrained by cost, complexity and latency. This creates an urgent need for a new approach that is fast, automated, precise and cost-effective. To address this gap, this study proposes the development of a 90mm autonomous MLRS platform equipped with smart missiles with thermal seekers, specifically designed to provide robust and responsive automatic protection for vital objects within a 5 km radius. This research focuses on analyzing the performance of a 90mm caliber Multi Launcher Missile System (MLRS) integrated with an anti-air attack radar system to protect vital strategic objects. This study was designed as an experimental research with a quantitative approach, where variables such as flight speed, navigation deviation, and fire accuracy were systematically measured. As part of the conceptual framework, library research was also conducted to review the theory, method of loiter control, and waypoint navigation system on drones, as well as previous studies related to the integration of light weapons on multirotor platforms. The results demonstrated that the MLRS maintained an interception accuracy rate above 95% in all scenarios. The system achieved effective firing distances between 16–20 km and radar detection ranges up to 40 km. The High-Speed Cruise Missile was identified as the most critical threat due to its extremely high speed and low-altitude profile, demanding rapid early detection, priority targeting, and salvo firing with minimal delay. Stealth drones also posed significant challenges due to their radar evasion capabilities. Visual data analysis through bar charts and pie charts confirmed that cruise missiles and stealth drones dominate threat severity. Overall, the MLRS proved highly effective, responsive, and adaptable, making it a robust and scalable solution for modern battlefield air defense against complex aerial threats.